Self-Efficacy of Instrument Nurse during the Assignment of Earthquake Disaster in Nusa Tenggara Barat (NTB) - Laily Hidayati; Andri Setiya Wahyudi; Achmad Tirmidzi (Universitas Airlangga, 2019)
Introduction: Nurse is the spearhead of hospital services at disaster, which is also links to the Integrated Emergency Response System (SPGDT). This study aims to describe self efficacy of instrument nurse during the assignment period. Method: The study used a qualitative design with descriptive phenomenology approach. The study population was instrument nurse assigned to the earthquake in West Nusa Tenggara (NTB), the study sample was obtained by snowball sampling, participants were 16 instrument nurse. Method of collecting data using in-depth interview. Data collection tools used are voice recorder, interview guideline, and field note. Data is processed by thematic analysis according to Colaizzi. Results: Nurses' self efficacy can be seen from a positive assessment of their capabilities as evidenced by expressing understanding, forming a team, and establishing an emergency response team. In addition, nurse have high motivation to do assignments, and nurse show a positive attitude when appointed to work in NTB. Discussion: Knowledge, attitudes, and motivation of nurses, will be build a nurse self efficacy. Nurses who have high self efficacy, are confident in their abilities in carrying out their duties, will be able to carry out their duties well despite the demands and high workload.